MICROWAVE IMAGING FOR DIELECTRIC OBJECTS UNDER THE BORN APPROXIMATION BASED ON PROJECTION - SUH, KW; KIM, SG; KIM, SY; RA, JW (JOHN WILEY & SONS INC, 1992)
Microwave imaging for dielectric objects under the Born approximation is suggested by using the computerized tomography based on projection. Limiting factors of degradation in reconstructed images are identified and explored in terms of projection function and necessary condition on the first-order Born approximation. To illustrate the usefulness of the presented method, simulation and experiment are performed in this article.